Assessing policy options for sustainable water use in India’s cereal production system - Singh, Vartika; Stevanović, Miodrag; Jha, Chandan Kumar; Beier, Felicitas; Ghosh, Ranjan Kumar; Lotze-Campen, Hermann; Popp, Alexander (IOP Publishing, 2023)
In India, the production of rice and wheat account for more than 80% of its total agricultural water use. As farming is highly dependent on water availability, rapidly receding water levels require urgent measures to manage withdrawals. We assess policy instruments that can reduce pressures on water resources, while at the same time limiting adverse impacts on water-intensive cereal production systems, land-use changes and economic welfare. To this end, we use a dynamic and integrated partial equilibrium model of agricultural production and its impact on the environment to reflect two options: an increase in energy costs for irrigation water (price-related effects), and alternatively, physical quotas on water withdrawals (quantity-related effects). We conclude that it is possible to increase energy prices for agriculture with minimal impacts on agricultural production, agricultural prices, and trade in cereal crops, and moderately reduce water withdrawals by 2050. We find that the intermediate effects of pricing policies are negative for all indicators as compared to quota policies. However, by 2050, both policies yield similar outcomes for all indicators. Our results offer insights into ways in which these policies drive different mechanisms and trade-offs on important agro-economic indicators, and they offer the choice for water conservation policy decision-making based on other critical factors such as implementation costs.